‘MAKING OUR LAW STUDENTS COMPREHEND FOREIGN LEGAL TERMINOLOGY: THE QUEST FOR IDENTIFYING FUNCTION, CONTEXT, THE SEMAINON AND THE SEMAINOMENON IN THE TEACHING OF COMPARATIVE LAW’ - PLATSAS, Antonios Emmanuel (Comparative Legilinguistics, 2017)
This paper will explore the implications in relation to the possibility of making law students comprehend foreign legal terminology. The starting point of our analysis, our hypothesis, will be that the law student is not necessarily equipped with foreign language skills. For this reason the author will attempt to demonstrate that comparative lawyers must familiarise their unfamiliarised (students of law) with familiar domestic[1] terminology where this is possible. If no such familiar concepts can be found, the comparative lawyer should attempt to proceed with ‘translating’ foreign legal concepts by the use of ‘close (functional) terminological equivalents’ in one’s domestic legal language (school of functionalism). If, on the other hand, no parallel legal devices for the foreign legal term are found in one’s domestic jurisdiction, the comparative lawyer should proceed by deploying a contextual approach in his analysis/teaching (school of contextualism). Above all, one is reminded that words are mere conventions. So too legal terms are mere conventions. As a result, it would be neglectful to not state that our students must be assisted in identifying the semainon (σημαίνον) and the semainomenon (σημαινόμενον), that is assisted in identifying the signified and the signifier, when they engage themselves with foreign legal terminology in their comparative law studies. Additionally, as Van Hoecke has argued, apparently disconnected notions, concepts or areas of law may well be relevant to each other (Van Hoecke 2004, 175). Yet, it would be perfectly ‘legitimate’ on certain occasions for one to compare prima facie connected terms such as ‘Interprétation – Interpretation or Construction – Auslegung’ respectively in French, English and German, since these terms are a perfectly valid comparative trio (all words basically refer to the same intellectual activity) (Platsas 2008, 6; quoting Van Hoecke, op. cit., n. 3). All in all, the paper will conclude that the comparative lawyer should be constantly reminded of the difficulties that his/her students might have when dealing with foreign legal terminology, because of one has it that even experienced comparative lawyers can face problems of comprehension when dealing with foreign legal terminology. [1] Cf. Zweigert and Kötz 1998, 35; according to them the comparatist can only reach ideal results, if he ‘eradicates the preconceptions of his native legal system.’